Analysis Of The Influence Of Occupational Safety Policy On Worker Injury Rate - Haryanta, Joko Tri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2017)
The Impact of Occupational Safety Policies on Worker Injuries is the guiding principle for this research. There were a total of 38 corenfindens used in this quantitative study, which also included descriptive analysis. The results of the ANOVA test showed that the Occupational Safety Policy has a significant impact on the Worker Injury Rate, with a significance level of 0.022 compared to α (0.05). As a result, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. Variables in Occupational Safety Policies and Their Effect on Worker Injuries.